The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1088/1361-6463/abe26d
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic wave-absorbing performance of carbons, carbides, oxides, ferrites and sulfides: review and perspective

Abstract: The development of electromagnetic wave-absorbing materials (EMWAMs) offers a promising way to address the ever-increasing issue of electromagnetic pollution. Up to now, significant efforts have been made to explore superior EMWAMs featuring strong absorption intensity, broad bandwidth, low density, and small thicknesses as well as those with exceptional performance. Therefore, in this paper, we offer a a comprehensive review summarizing the recent inspiring advancements in various EMWAMs, including those base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 198 publications
0
17
0
Order By: Relevance
“…Though plentiful excellent reviews have been reported to introduce the advances of EM wave absorbing materials, [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] they mainly focus on introducing EM wave loss materials on basis of material categories, such as carbon materials, [ 43 , 44 , 45 , 46 , 47 , 48 ] MOFs deprived materials, [ 49 , 50 , 51 ] boron nitride, [ 52 ] conducting polymers, [ 53 , 54 ] ferrites, [ 55 , 56 , 57 ] sulfides, [ 58 ] and MXene [ 59 , 60 , 61 ] or design of peculiar micro/nanostructure. [ 62 ] As far as we know, the topic that lies on EM wave loss mechanisms and models has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Though plentiful excellent reviews have been reported to introduce the advances of EM wave absorbing materials, [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] they mainly focus on introducing EM wave loss materials on basis of material categories, such as carbon materials, [ 43 , 44 , 45 , 46 , 47 , 48 ] MOFs deprived materials, [ 49 , 50 , 51 ] boron nitride, [ 52 ] conducting polymers, [ 53 , 54 ] ferrites, [ 55 , 56 , 57 ] sulfides, [ 58 ] and MXene [ 59 , 60 , 61 ] or design of peculiar micro/nanostructure. [ 62 ] As far as we know, the topic that lies on EM wave loss mechanisms and models has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, optimized multiple-component construction was expected to cause significant changes in the number and distribution of heterointerfaces. [36,37] Thus, the redistribution and accumulation of charges in these interfaces would be promoted and result in enhanced interfacial polarization. [38,39] More significantly, the anion exchange reaction between F − and the other anions could cause a drastic dislocation in atoms during the new phase formation process.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, biomass-derived materials have emerged as light-weight, low-cost, and green microwave absorbers, which their fascinating microwave characteristics are originated from their dielectric and conductive properties 29 , 34 . Nowadays, apart from carbon-based structures, various structures including transition metal carbides and nitrides (MXenes), metal–organic framework (MOF)-derived materials, nanostructured metals and oxides, as well as other conductive polymers comprising polyaniline, polypyrrole, polythiophene, and polydopamine were enormously used as microwave absorbing materials 35 44 . It should be noted that the cobalt-based spinel oxides have exhibited salient microwave absorbing features meanwhile the sulfide nanostructures have recently intrigued a great deal of interest due to their considerable relaxation loss features, generated by their narrow energy band gaps 45 47 .…”
Section: Introductionmentioning
confidence: 99%